Neuronal ceroid-lipofuscinosis, a type of amaurotic family idiocy: clinical and pathological study of four cases - Luciano de Souza Queiroz; Joaquim N. da Cruz Neto; J. Lopes de Faria (Arquivos de Neuro-Psiquiatria)
Neuronal ceroid-lipofuscinosis (NCL) is a recent term, proposed for acurate designation of the late-onset types of Amaurotic Family Idiocy (AFI). Histopathology shows ubiquitous intraneuronal accumulation of lipopigments, being the most important factor for characterization of the entity at present time. Biochemical changes and pathogenesis are obscure. NCL is in contrast to the infantile type of AFI (Tay-Sachs disease), in which intraneuronal accumulation of gangliosides (sphingolipids) is due to the well known deficiency of a lysosomal enzyme. The authors report on four cases of NCL, two brothers of the late infantile (Jansky-Bielschowsky) type and a brother and a sister of the juvenile (Spielmeyer-Sjögren) type. One autopsy and three cortical biopsies revealed moderate to severe distention of the neurons by lipopigment, with nerve cell loss, gliosis and cerebral atrophy. Lipopigment was also increased in liver, heart and spleen. The patients were the first in Brazilian literature in whom the storage material was identified as lipopigment by histochemical methods. A brief summary of the clinical features of NCL is presented, and relevant problems are discussed, concerning interpretation of the nature of the storage material, and significance of the disease for gerontological research.